A brief history of history: some models of history and lessons for leadership and management' - Sharma, Subhash (2005)
Taking a managerial perspective, this article presents some models of history with a view to draw lessons for leadership and management of organizations and institutions. The suggested models include: evolution of human thought in terms of religions, science and spirituality and their convergence; transitions in society from kingdom-state to nation-state to corporates as state and beyond; creativity view of history; dignity struggle and liberation view of history; `fall of the fittest' view of history; and the swastika analysis of history. The article explores the implications of these models for providing enlightened leadership to organizations and society by creating synergy between influences from the West and the East. - Reproduced.
Keywords: Organizations; Management; Leadership